Understanding gen z and gen x responses to influencer communications - Danijel Bratina; Armand Faganel (Administrative Sciences, 2024)
The increased popularity of social media has greatly affected the marketing-communications activities of companies. This study seeks to understand how influencers promoting products affect their followers' purchasing intentions and attitudes towards endorsed products. Our main interest is to get an insight on differences between two generations (X and Z). We construct a structural model, based on the theory of credibility. Findings suggest that influencer endorsements have an impact on both age groups, with a more noticeable effect observed in the younger generation. The loyalty towards influencers emerges as a constructive intermediary factor, amplifying the influence of credibility on purchasing intentions across both generations. When considering attitudes towards the brands endorsed by the influencers, loyalty's impact is comparatively modest. The results provide a building block in understanding the influencers' activities in marketing-communications, and how they can be used for communication with different generations.
Keywords: 350; effectiveness of influencers' marketing-communications; Gen X; Gen Z; influencer marketing